Proposal for the implementation of post-consumer reverse logistics practices in the treatment of solid waste: a multi-case study in the textile and clothing sector of Santa Cruz do Capibaribe - Nascimento, Aline da Silva; Gonçalves, Anderson Tiago Peixoto (Brazilian Journal of Production Engineering, 2023)
The study aims to propose the implementation of post-consumer reverse logistics practices in the treatment of solid waste from microenterprises in the textile and clothing sector in Santa Cruz do Capibaribe. For that, it was necessary to know the productive process of the companies; identify the solid residues that are generated in the production process; raise the actions that are currently adopted by companies regarding the treatment of their solid waste; and, finally, propose new actions for the treatment of solid waste generated in the production process. This is an applied, qualitative, exploratory and descriptive research, in the format of a multicase study, which used a semi-structured interview script and non-participant observation as a data collection instrument. After knowing the reality of the two companies, it was concluded that there is a long way to go in the search for the implementation of Post-Consumer Reverse Logistics practices. It was noticed that their efforts, aiming at the correct disposal of solid waste generated in the production process, are insufficient, since they adopt few treatment actions, giving rise to the incorrect disposal of a high volume of materials. Thus, actions were proposed for the treatment of this solid waste, involving resale, recycling, reuse and a more appropriate final destination.
Keywords: Reverse Logistics; Solid Waste Treatment; Analysis and problem solving